International validation of the revised European Organisation for Research and Treatment of Cancer Head and Neck Cancer Module, the EORTC QLQ‐HN43: Phase IV - Singer, Susanne; Baumann, Ingo (Head & neck, 2019)
Background - We validated the new European Organisation for Research and Treatment of Cancer Quality of Life Head and Neck Module (EORTC QLQ‐HN43). - - Methods - We enrolled 812 patients with head and nec...